Four ways from universal to particular: how Chomsky's principles-and-parameters model is not selectionist. Issue 3 (2nd July 2016) - Ellerman, David P.
Abstract : Following the development of the selectionist theory of the immune system, there was an attempt to characterise many biological mechanisms as being 'selectionist' as juxtaposed with 'instructionist'. However, this broad definition would group Darwinian evolution, the immune system, embryonic development, and Chomsky's principles-and-parameters (P&P) language-acquisition mechanism together under the 'selectionist' umbrella, even though Chomsky's mechanism and embryonic development are significantly different from the selectionist mechanisms of biological evolution and the immune system. Surprisingly, there is an abstract way using two dual mathematical logics to make the distinction between genuinely selectionist mechanisms and what are better called 'generative' or symmetry-breaking mechanisms. This distinction is outlined in this note.